2011
DOI: 10.1016/j.taap.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Induction of NEIL1 and NEIL2 DNA glycosylases in aniline-induced splenic toxicity

Abstract: The mechanisms by which aniline exposure elicits splenotoxic response, especially the tumorigenic response, are not well-understood. Earlier, we have shown that aniline-induced oxidative stress is associated with increased oxidative DNA damage in rat spleen. The base excision repair (BER) pathway is the major mechanism for the repair of oxidative DNA base lesions, and we have shown an up-regulation of 8-oxoguanine glycosylase 1 (OGG1), a specific DNA glycosylase involved in the removal of 8-hydroxy-2′-deoxygua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 41 publications
(74 reference statements)
2
28
0
3
Order By: Relevance
“…Furthermore, we have also shown that NEILs, which are distinct from OGG1 in structural features and reaction mechanisms, and which act on different substrates (Dou et al, 2003; Englander and Ma, 2006, Ma et al, 2011), are also involved in the repair of aniline-induced DNA damage in the spleen of aniline-treated rats. Although the role of NTH1 and APE1 in DNA repair and transcriptional regulation has been widely investigated, the roles of NTH1 and APE1 in the regulation of aniline-induced splenotoxic response have not been evaluated.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Furthermore, we have also shown that NEILs, which are distinct from OGG1 in structural features and reaction mechanisms, and which act on different substrates (Dou et al, 2003; Englander and Ma, 2006, Ma et al, 2011), are also involved in the repair of aniline-induced DNA damage in the spleen of aniline-treated rats. Although the role of NTH1 and APE1 in DNA repair and transcriptional regulation has been widely investigated, the roles of NTH1 and APE1 in the regulation of aniline-induced splenotoxic response have not been evaluated.…”
Section: Introductionmentioning
confidence: 83%
“…Earlier studies from our laboratory have shown that aniline exposure results in iron overload and oxidative stress in the spleen (Khan et al, 1997, 1999, 2003a, 2003b). More importantly, our studies have shown increased oxidative DNA damage in the spleen of rats following aniline exposure (Wu et al, 2005; Ma et al, 2008, 2011), which could potentially lead to mutagenic and/or carcinogenic responses.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, transcriptome analyses of tissue from rats fed quercetin showed an induction of Mutyh expression [48,81]. Levels of Neil1 mRNA have been shown to be elevated following ROS [43] and aniline treatments [143]. …”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%